å°å°¼å¤ç”¸ã€ŠåŽè¯ã€‹æ•™æä½¿ç”¨æƒ…å†µè°ƒæŸ¥åˆ†æžâ€”â€”ä»¥å–„ç‰§é«˜ä¸ä¸ŽTARUNA BUMI KHATULISTISWAé«˜ä¸ä¸ºä¾‹ - (F13110022), Robin; ., Ina; Tjen, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
ã€ŠHuayuã€‹is a teaching material that compiled by China and Indonesiaâ€™s Chinese Education experts. Indonesiaâ€™s government recommended each Senior High School use these books as their Chinese subject Teaching Material. This thesis uses the books as research object and chose Gembala Baik and Taruna Bumi Khatulistiwa Senior High Schoolâ€™s students and teachers as its survey object. Writer analyzed these booksâ€™ contents, distributed the questioners to two schoolâ€™s students, and interviewed the teachers, thereby found out these booksâ€™ strong points and weak points. Through research, writer concluded that Gembala Baik and Taruna Bumi Khatulistiwaâ€™s students and teachers considerã€ŠHuayuã€‹as the most appropriate books for teaching chinese. These booksâ€™ contents is more scientific, useful, purpose, student oriented and interesting. Keywords: ã€ŠHuayuã€‹text book teaching material analyzeÂ Â Â Â Â studentâ€™s assessmentÂ Â teacherâ€™s assessmentæ‘˜è¦:ã€ŠåŽè¯ã€‹æ˜¯ç”±ä¸å›½å°å°¼ä¸¤å›½çš„åŽè¯æ•™å¦ä¸“å®¶ä¸€èµ·ç¼–å†™çš„æ±‰è¯æ•™æã€‚Â Â å°å°¼æ”¿åºœæŽ¨èå„å¤§å°å°¼é«˜ä¸ä½¿ç”¨è¯¥å¥—æ•™æã€‚æœ¬æ–‡ä»¥ä¸å›½æ•™è‚²ç§‘å¦å‡ºç‰ˆç¤¾çš„ã€ŠåŽè¯ã€‹ä¸ºä¸»è¦ç ”ç©¶å¯¹è±¡ä»¥åŠé€‰å–ä¸¤æ‰€å¦æ ¡ï¼šå–„ç‰§ä¸ŽTARUNA BUMI KHATULISTIWAé«˜ä¸çš„å¦ç”Ÿå’Œæ±‰è¯æ•™å¸ˆä½œä¸ºä½¿ç”¨è€…è°ƒæŸ¥å¯¹è±¡ã€‚ç¬”è€…åˆ†æžÂ æ•™æå†…å®¹ï¼Œå‘ä¸¤æ‰€å¦æ ¡çš„å¦ç”Ÿåˆ†å‘è°ƒæŸ¥é—®å·ä»¥åŠå‘æ•™å¸ˆä»¬è¿›è¡Œè®¿è°ˆï¼Œä»Žè€Œ äº†è§£å¹¶å‘çŽ°è¯¥æ•™æçš„ä¼˜ç‚¹ä¸Žä¸è¶³ä¹‹å¤„ã€‚ç»è¿‡ç ”ç©¶ï¼Œç¬”è€…å¾—å‡ºçš„ç»“è®ºæ˜¯å–„ç‰§ä¸ŽTARUNA BUMI KHATULISTIWAé«˜ä¸çš„å¸ˆç”Ÿä»¬è®¤ä¸ºã€ŠåŽè¯ã€‹æ˜¯ä¸€å¥—æ¯”è¾ƒå¥½çš„æ•™æå¹¶ä¸”é€‚åˆä»–ä»¬ä½¿ç”¨ã€‚è¯¥æ•™æçš„å†…å®¹ä¹Ÿç¬¦åˆç§‘å¦æ€§ã€å®žç”¨æ€§ã€é’ˆå¯¹æ€§åŠè¶£å‘³æ€§ã€‚æ•´ä½“æ¥çœ‹ï¼Œã€ŠåŽè¯ã€‹æ˜¯ä¸€å¥—èƒ½æŽ¨åŠ¨å°å°¼é«˜ä¸æ±‰è¯æ•™å¦çš„å¼€å±•ã€ æ„ä¹‰é‡å¤§çš„æ•™æã€‚ å…³é”®è¯ï¼šã€ŠåŽè¯ã€‹æ•™æ æ•™æåˆ†æž å¦ç”Ÿè¯„ä»· æ•™å¸ˆè¯„ä»·